(untitled) (Bangladesh Journal of Medical Science, 2025)
Background To overcome the problem of urinary tract infections (UTIs) caused by antibiotic resistant E. coli (EC), either new drugs should be discovered or traditional, forgotten antibiotic options like fosfomycin should be reconsidered. This systematic review enlightens the usage of fosfomycin in different countries and based on the recommendations, seek to find the applicability of using fosfomycin as a first line drug of choice in Sri Lanka like settings. Method A systematic review of literature following the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis was conducted from 1st of January 2011 to 31st of December 2021 in PubMed using different search terms. Initially, 498 potentially relevant articles were identified. Out of which, 29 articles were included in this review, based on inclusion and exclusion criteria. Results Out of 29, 18 studies reported fosfomycin sensitivity data, accounting for total of 14,306 bacterial isolates. Majority of the isolates were E. coli (n=9806) followed by Klebsiella spp. (n=1444). All these studies reported more than 80% sensitivty to fosfomycin, out of which 11 studies reported fosfomycin resistance ranging from 0.19% to 22%. Conclusions Multi-drug resistant, extended spectrum of β-lactamase (ESBL) producing bacteria are increasingly reported. Fosfomycin is the most effective antibiotic against ESBL-EC with a high sensitivity rate against urinary isolates of both community and hospital-acquired UTIs. The findings shed some light on the applicability of fosfomycin as a potential treatment option against E. coli in countries with a high burden of antibiotic resistance. However, further clinical studies should be performed before administration. Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 395-405